Pengembangan Media Flashcard Materi Makanan Bergizi Seimbang untuk Siswa Kelas IV di SDN 26 Mataram - Nanda Intan Islami; Prayogi Dwina Angga; Setiani Novitasari (Mataram University, 2026)
Students' understanding of balanced nutrition remains relatively low because learning is still supported by limited instructional media that are less interactive. Therefore, developing an engaging learning medium is necessary to help students understand balanced nutrition concepts more effectively. This study aims to determine the validity and practicality of flashcard media for teaching balanced nutrition to Grade IV students of SDN 26 Mataram. The method used in this study is Research and Development (R&D) with a 4D model consisting of define, design, develop, and disseminate. The subjects in this study were 30 Grade IV students and one teacher of SDN 26 Mataram. The object of this study was flashcard media designed to assist students in understanding balanced nutrition material through the use of traditional Sasak food examples and educational games. The data analysis techniques used were descriptive qualitative and quantitative. Data were collected using observation sheets, interview sheets, preliminary understanding tests, validity questionnaires, and practicality questionnaires. The results showed that the media expert validation score was 81.25%, categorized as fairly valid, while the material expert validation score was 100%, categorized as very valid. The practicality level based on student responses in Trial I was 92.5%, categorized as very practical, and in Trial II was 98.13%, categorized as very practical. Furthermore, based on teacher responses in Trial I, the practicality score was 95.31%, categorized as very practical, and in Trial II, the practicality score was 98.44%, categorized as very practical. Based on these results, the developed flashcard media was categorized as very valid and very practical, indicating that it can be used as a learning medium for teaching balanced nutrition to Grade IV students of SDN 26 Mataram.